STRIVING FOR SUPERIORITY SHOWN BY AIBELEEN IN THE MOVIE THE HELP - PRAMONO, HAEKAL HENDRO (Jurnal Ilmiah Mahasiswa FIB, 2013)
Striving for superiority is a theory proposed by a well-known expertnamed Alfred Adler. This theory shows the struggle of human-being to achievesucces. The Help is one of movies showing the struggle of a maid, AibeleenClark, to fight for her right as a human-being. This study aims at finding out howthe striving for superiority is applied by Aibeelen in the movie "The Help".This study was classified as a qualitative reseach. The data in this studywere taken from scenes of the movie The Help which illustrated each process ofAibeleen’s struggle to achieve success or superiority. In data analysis, the writeranalysed scenes in the movie which showed the process of striving for superiorityin the character of Aibeleen.The result of this study shows that all of the processes in Adler’s theory isobviously applied by the character of Aibeleen in The Help. There are five pointsof proccesses proposed by Adler: from the inferiority side, the final goal, thestriving force as compensation, and as a result, shows the striving for individualsuccess or her strive for success.The conclusion of this study shows that every people has the steps ofstriving for success or superiority, as seen in The Help. The analysis done by thereseacher shows that the character of Aibeleen in The Help undergoes the phasesof her life where she fights for a goal to achieve her superiority. The reseachersuggests that other reseachers analyse the characters in this movie using differenttheories, such as self-actualization proposed by Maslow. Keywords: striving for superiority, Alfred Adler, The Help, Aibeleen Clark.